INSTITUTIONAL OWNERSHIP AND TAX AVOIDANCE: COMPARATIVE STUDY IN BUMN (BADAN USAHA MILIK NEGARA) AND PRIVATE COMPANIES: Comparative Study in BUMN (State-Owned) and Private Companies - Ellyzabeth Putri Vizandra; Elia Mustikasari (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2021)
This study aims to provide empirical evidence regarding the effect of institutional ownership on tax avoidance and differences in tax avoidance in state-owned and private companies. This study uses a quantitative approach with explanatory and comparative methods. The sample of this research is state-owned and private companies listed on the Indonesia Stock Exchange from 2014 to 2018 with a total of 60 companies. The sampling technique in this study uses a purposive sampling method. Hypothesis testing in this study uses Multiple Regression Linear Analysis to examine the effect of institutional ownership on tax avoidance and uses the Independent Sample T-Test to examine differences in tax avoidance in BUMN and private. The results of this study indicate that institutional ownership has no effect on the practice of corporate tax avoidance. This study also finds that there is no significant difference in tax avoidance practices in state-owned and private companies. The results of this study are expected to be suggestions for shareholders, especially institutional ownership to improve their monitoring function to the management to minimize tax avoidance. In addition, the government is expected to provide supervision with the same proportions, both to BUMN and private companies.